Time course changes in selected biochemical indices of broilers in response to pretransport handling - Voslarova, E; Chloupek, P; Vosmerova, P; Chloupek, J; Bedanova, I; Vecerek, V (Poultry science, 2011)
Two experiments were conducted to assess the stress response of broilers to catching and pretransport handling followed by different periods of crating. The short-term changes in selected biochemical indices were monitored at 1-min intervals within 10 min of crating after the catching and handling of broilers (experiment 1). These indices were further monitored at 15-min intervals for 2 h of crating after the catching and handling of broilers (experiment 2). Increased (P < 0.001) corticosterone concentrations were observed immediately after the broilers were caught, handled, and placed in crates. They continued to increase until 7 min after crating and then slowly decreased, but even at 120 min after handling, corticosterone concentrations were higher (P < 0.001) in crated broilers than in control broilers. In addition, lactate concentrations increased (P < 0.001) immediately in comparison with those of broilers with no additional handling except for catching and blood sampling, but 15 min later, the lactate concentrations had decreased to the precrating level. Lactate dehydrogenase concentrations increased (P = 0.042) 30 min after crating and continued to increase for the rest of the monitored period. A decreased level of cholesterol (P = 0.017) and increased concentration of uric acid (P = 0.041) were found 1 min after crating. The decrease in cholesterol was visible up to 9 min after crating; it then returned to its original value except for the period from 75 to 90 min after crating, when a decrease (P < 0.05) was again detected. Higher (P < 0.01) concentrations of uric acid were found continuously from 4 to 75 min after crating. Glucose concentrations were increased (P = 0.017) 2 min after crating, but the stress-induced increase was not consistent over the course of the next few minutes after crating. Glucose concentrations were not different from those of control broilers from 10 to 120 min after crating, although they showed a decreasing pattern. A decrease (P = 0.031) in triglyceride concentrations was detected 75 min after crating.
Keywords: kortikosteron; Uric Acid; fyziologický stres; Cholesterol; Triglycerides; cholesterol; Chickens; Transportation; Lactic Acid; doprava; Corticosterone; kyselina močová; Biomarkers; Blood Glucose; zvířata; Stress, Physiological; Kinetics; kur domácí; triglyceridy; L-Lactate Dehydrogenase; biologické markery; Handling, Psychological; krevní glukóza; Animals; L-laktátdehydrogenasa; kyselina mléčná; handling (psychologie); kinetika